Study on the Effect of Sulfuric Acid Addition on the Porosity and Permeability Properties of Nata De Soya Porous Membranes - Lailatul Qodriyah, Nur; Masturi, Masturi; Harnina Bintari, Siti; Aji, Mahardika Prasetya (Universitas Negeri Malang, 2024)
Porous nata de soya membranes are a promising filtration material due to their good mechanical and chemical properties. However, further modifications are necessary to enhance their filtration performance, one of which involves the addition of sulfuric acid. Therefore, the objective of this study is to investigate the effect of sulfuric acid addition on the porosity and permeability properties of porous nata de soya membranes. Porosity tests using Scanning Electron Microscope (SEM) were conducted to analyze the microstructure of the nata de soya membranes. The SEM characterization results provide detailed images of the membrane's pore structure, including size, distribution, surface area, and pore density. Additionally, permeability analysis was performed using Darcy's law. The results indicate that the addition of sulfuric acid affects the porosity and permeability of the membranes. Increasing the sulfuric acid concentration from 15% to 25% resulted in a decrease in porosity from 51% to 47%. The pore size increased from 0.35 µm at 15% to 0.86 µm at 25%. Furthermore, the surface area and pore density decreased with the increasing concentration of sulfuric acid, indicating a reduction in membrane effectiveness in filtration processes. The membrane's permeability decreased drastically from 2.55287 x 10-9 m² at 15% to 2.12739 x 10-12 m² at 25%, demonstrating that sulfuric acid causes pore closure and structural damage to the membrane, reducing its ability to allow fluid to pass through. The implications of this research suggest that porous nata de soya membranes are effective for microfiltration of bacteria (such as E. coli) and wastewater filtration.